2020
DOI: 10.1016/j.cub.2020.08.081
|View full text |Cite
|
Sign up to set email alerts
|

The Recovery, Interpretation and Use of Ancient Pathogen Genomes

Abstract: The ability to sequence genomes from ancient biological material has provided a rich source of information for evolutionary biology and engaged considerable public interest. Although most studies of ancient genomes have focused on vertebrates, particularly archaic humans, newer technologies allow the capture of microbial pathogens and microbiomes from ancient and historical human and non-human remains. This coming of age has been made possible by techniques that allow the preferential capture and amplification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 145 publications
(234 reference statements)
0
19
0
Order By: Relevance
“…Research on pathogen aDNA often highlights how human and pathogen evolutionary trajectories are entangled, and point to key events – societal changes, migration of people – through which humans and pathogens affect one another. For example, a recent review of ancient pathogen genomics published in the journal Current Biology describes how, in the case of “ S. enterica and Y. pestis , the ancient presence of virulence factors indicates that subsequent decline in their incidence and disease severity was most likely driven by changes in human behaviour and pathogen ecology” (Duchêne et al., 2020: R1224). Another review published in Microbial Genomics asks “how have human–microbe interactions influenced the evolution of each species” and suggests that “aDNA studies have precipitated a major revision to our understanding of recent human and bacterial evolution, for example the spread of steppe ancestry across Eurasia, and the plagues carried with it” (Arning and Wilson, 2020: 15).…”
Section: Multispecies Entanglements As a Historical Forcementioning
confidence: 99%
See 3 more Smart Citations
“…Research on pathogen aDNA often highlights how human and pathogen evolutionary trajectories are entangled, and point to key events – societal changes, migration of people – through which humans and pathogens affect one another. For example, a recent review of ancient pathogen genomics published in the journal Current Biology describes how, in the case of “ S. enterica and Y. pestis , the ancient presence of virulence factors indicates that subsequent decline in their incidence and disease severity was most likely driven by changes in human behaviour and pathogen ecology” (Duchêne et al., 2020: R1224). Another review published in Microbial Genomics asks “how have human–microbe interactions influenced the evolution of each species” and suggests that “aDNA studies have precipitated a major revision to our understanding of recent human and bacterial evolution, for example the spread of steppe ancestry across Eurasia, and the plagues carried with it” (Arning and Wilson, 2020: 15).…”
Section: Multispecies Entanglements As a Historical Forcementioning
confidence: 99%
“…For example, in the case of an 800-year-old grave in Trondheim in Norway, ancient pathogen analysis suggested that "salmonellosis was a deadly invasive disease of humans for centuries before its first recognition by physicians" (Zhou et al, 2018(Zhou et al, : 2424. Ancient pathogen genomics has also provided information on the co-presence and co-circulation of multiple pathogens in specific historical contexts (Arning and Wilson, 2020;Ducheˆne et al, 2020). Some have argued that ancient pathogen genomics has also potential relevance for biomedicine by allowing scientists to understand processes through which bacteria and viruses evolve over time and thus better estimate the ecological conditions and genetic mechanisms through which modern strains may increase in virulence (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…We are delighted to see that the broad phylogenetic findings and interpretation as presented in our work "The origins and genomic diversity of American Civil War Era smallpox vaccine strains" have been reproduced by Brinkmann and colleagues (Brinkmann A, Souza ARV, Esparza J, Nitsche A, Damaso CR: Re-assembly of 19thcentury smallpox vaccine genomes reveals the contemporaneous use of horsepox and horsepox-related viruses in the United States, in preparation) [1]. While the libraries we generated from the vaccination kits likely contain DNA fragments representing the entire genomic content, we question the ability to faithfully reconstruct these termini given the following, well-characterized aspects of ancient DNA (aDNA): (i) The DNA is heavily truncated to median fragments sizes less than 55 bp, (ii) is mixed with the DNA of many different species, and (iii) has damaged nucleotides, features which all complicate mapping and de novo assemblies [2,3]. These factors exacerbate the fundamental difficulties of re-assembling genomic repetitive elements and regions [4], thereby creating de novo assemblies which are both considerably shorter than full genome length and prone to spurious contigs.…”
Section: To the Editormentioning
confidence: 99%